2003
DOI: 10.1249/01.mss.0000069752.96438.b0
|View full text |Cite
|
Sign up to set email alerts
|

Strength Increase after Whole-Body Vibration Compared with Resistance Training

Abstract: WBV, and the reflexive muscle contraction it provokes, has the potential to induce strength gain in knee extensors of previously untrained females to the same extent as resistance training at moderate intensity. It was clearly shown that strength increases after WBV training are not attributable to a placebo effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
565
11
42

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 593 publications
(667 citation statements)
references
References 21 publications
(27 reference statements)
49
565
11
42
Order By: Relevance
“…Consistent with the present study, muscle strength improvements (7.2-9.0%) have been reported after 12 to 24 weeks of static and dynamic exercises with WBV in young women. 16,17 Our findings are in agreement with a 2.2% increase in body fat-free mass reported in young women after 24 weeks of unloaded static and dynamic exercises with WBV. 17 Because the increase in LST mass after 6 weeks of WBV training was no different than the CON period in our study, muscle strength gains would be primarily attributed to neural adaptations rather than muscle hypertrophy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with the present study, muscle strength improvements (7.2-9.0%) have been reported after 12 to 24 weeks of static and dynamic exercises with WBV in young women. 16,17 Our findings are in agreement with a 2.2% increase in body fat-free mass reported in young women after 24 weeks of unloaded static and dynamic exercises with WBV. 17 Because the increase in LST mass after 6 weeks of WBV training was no different than the CON period in our study, muscle strength gains would be primarily attributed to neural adaptations rather than muscle hypertrophy.…”
Section: Discussionsupporting
confidence: 89%
“…17 Because the increase in LST mass after 6 weeks of WBV training was no different than the CON period in our study, muscle strength gains would be primarily attributed to neural adaptations rather than muscle hypertrophy. 16,17,19 Indeed, increased muscle strength per se may offer protection from obesity. 11 In addition, Bogaerts et al 41 showed improvements in muscle strength and oxygen consumption after WBV training that included static and dynamic exercises that were comparable to a fitness group that combined RET and aerobic training, suggesting that WBV training is an efficient alternative for overall training effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy individuals, some positive effects are reported, for example increased muscle strength in untrained females, 4 improved balance, muscle strength or gait performance in the elderly 5,6 whereas other studies have found no or insufficient effects of WBV training. 7,8 In individuals with stroke or other neurological diseases, few studies have evaluated the effects of WBV training and the results differ also in those studies.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…The vibrations are believed to initiate muscle contractions by stimulating the muscle spindles and the alpha motor neurons and thereby to have an effect similar to that of conventional training, such as resistance training. 4 Despite being on the market for over a decade there are no clear recommendations on how WBV training should be performed with regard to length of training, intensity, frequency or amplitude-setting.…”
Section: List Of Abbreviationsmentioning
confidence: 99%